INVESTIGATING THE USE OF ARTICLE ON SHERLOCK HOLMES: A STUDY IN SCARLET BY ARTHUR CONAN DOYLE - Rizki Silvia Ariyani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
Understanding the linguistic and literature pattern is essential for EFL students. The readers would know how to correctly use the part of speech in literature and the educational context. There are many types of speech, such as an article or known as a determiner. The article is a member of speech used with noun phrases to mark the identifiability of noun phrases' references.Sherlock Holmes is a fictional character that was created by a Scottish writer named Arthur Conan Doyle. Holmes is describing the prototype of the modern mastermind detective. In each novel, there is no doubt if the researcher will use one part of speech that dominates his/her novel. Whether it can be a verb, adjective, adverb, and even a straightforward form from the part of speech such as article or determiner, here, the researcher chooses to identify the use of an article in the novel Sherlock Holmes: A Study In Scarlet by Arthur Conan Doyle because researcher believes that study on the using of an article in a novel is still in short contact.